Pengembangan Sistem Informasi Agen Travel untuk Ticketing dan Administrasi Data menggunakan Metode Rational Unified Process (RUP) pada Mitra Original Group - Agustin Primawati; Yusi Tyroni Mursityo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mitra Original Group is one of the ground transportation services company that provides inter-city travel Services, package delivery service according to travel route, and fleet Charter. These services make the administration of data as important in operational activities, but the still conventional operational activities become a barrier for the company in conducting complete data administration. Based on the problem, the company needs to improve performance in operational activities. Performance enhancement can be assisted by the information System (SI) of travel agents related to the ticketing process and data administration to be developed in this research. The application of Rational Unified Process method is suitable because it is included in iterative development so that it can define the change in system needs well. System development is done through four phases, namely inception generate business processes and 9 system features, elaboration resulted in system design with Unified Modeling Language, Construction produces SI that implemented using CodeIgniter Framework, then conduct validation tests that result in the functionality of the system running properly, further testing system compatibility indicating that the system can run well on some browsers, as well as The transition phase performs the usability testing resulting in a score of 80.5. It shows that the SI interface is easy to understand and use by users.